Toksoplasmosis Serebral Pada Pasien dengan HIV/AIDS: Laporan Kasus - Mardaningrat, Gede Ari Mahendra; Pramartha, Dwiputra Yogi; Darmiastini, Ni Komang (Talenta Publisher, 2024)
Background: Toxoplasma encephalitis (ET) is the most common opportunistic infection that causes encephalitis or focal cerebral lesions in HIV/AIDS sufferers which occurs in approximately 3% to 40% of patients. Case Ilustration: A 39 years old male patient was brought to the Emergency Room (IGD) with complaints of weakness in the left hand and leg for 2 days before entering the hospital. Complaints of weakness in the left hand and leg were felt suddenly when the patient was about to move, as well as headaches that seemed to be pressing in almost all areas of the head since the previous month. On physical examination, candidiasis was found in the mouth area and redness on both hands and feet. Lab examination results showed CD4 levels of 68 cells/ÂµL and anti-toxoplasma IgG 156.10 IU/mL. CT scan of the head shows several lesions occupying space in the right and left frontal lobes, left basal ganglia, right cerebellar hemisphere. The patient was diagnosed with cerebral toxoplasmosis accompanied by stage IV HIV. Discussion: Toxoplasma encephalitis (ET) is a form of central nervous system complication in HIV/AIDS patients. This condition is the most frequent cause of focal intracerebral lesions in patients. Serological examination has an important role in establishing a diagnosis in patients with ET quality. Conclusion: Comprehensive management is the key to success in treating patients with toxoplasma encephalitis (ET) accompanied by HIV/AIDS Keyword: AIDS, CD4, HIV, Toxoplasma Encephalitis Latar Belakang: Ensefalitis toksoplasma (ET) adalah infeksi oportunistik paling umum yang menyebabkan ensefalitis atau lesi serebral fokal pada penderita HIV/AIDS yang terjadi di sekitar 3% hingga 40% pasien. Ilustrasi Kasus: Seorang pasien laki-laki berusia 39 tahun dibawa ke Instalasi Gawat Darurat (IGD) dengan keluhan lemah pada tangan dan kaki kiri sejak 2 hari sebelum masuk rumah sakit. Keluhan lemah pada tangan dan kaki kiri dirasakan mendadak ketika pasien hendak beraktivitas serta nyeri kepala yang seperti tertekan di hampir seluruh area kepala sejak 1 bulan. Pada pemeriksaan fisik ditemukan adanya kandidiasis pada daerah mulut serta kemerahan pada kedua tangan dan kaki. Hasil pemeriksaan lab menunjukkan kadar CD4 68 sel/ÂµL dan IgG anti toksoplasma 156,10 IU/mL. CT Scan kepala menunjukkan adanya gambaran beberapa space occupying lesion di lobus frontal kanan kiri, basal ganglia kiri, hemisfer cerebellum kanan. Pasien didiagnosis dengan toxoplasmosis serebri disertai dengan HIV stadium IV. Pembahasan: Ensefalitis toksoplasma (ET) merupakan bentuk komplikasi sistem saraf pusat pada pasien dengan HIV/AIDS. Kondisi ini adalah penyebab paling sering dari adanya lesi intraserebral fokal pada pasien. Pemeriksaan serologi memiliki peranan penting dalam menegakkan diagnosis pada pasien dengan kecurigaan ET. Kesimpulan: Penatalaksanaan yang komprehensif merupakan kunci dari keberhasilan dalam terapi pasien dengan ensefalitis toksoplasma (ET) disertai HIV/AIDS. Keyword: AIDS, CD4, Ensefalitis Toksoplasma, HIV